Adaptive and robust controls for static excitation systems. Issue 3 (5th May 2015) - Demenko, Ivo Doležel, Kay Hameyer, Wojciech Pietrowski; Krzysztof Zawirski, Andrzej; Ritonja, Jožef; Dolinar, Drago; Polajžer, Boštjan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Oscillations and related stability problems of synchronous generators are harmful and can lead to power outage. Studies have shown that currently available commercial applications of power system stabilizers (PSSs) do not ensure damping of modern generators operating in contemporary power systems at peak performances. The purpose of this paper is to contribute to development of the new PSS, which would replace currently used linear stabilizers. Design/methodology/approach – A synthesis of theoretical research, numerical simulations and laboratory experiments was the basic framework. Findings – Within a problem analysis, it was empirically confirmed that the currently used PSSs are not up to the needs of the present power systems. Based on an analysis of the contemporary solutions, it was found out that the most appropriate solutions are adaptive control and robust control. In this paper, the robust sliding mode theory was implemented for the PSS design. Research limitations/implications – The most notable restriction of rapid transfer of scientific solutions into a practice represents limited testing of proposed solutions on synchronous generators in power plants. Practical implications – The new PSS which would replace currently used conventional stabilizers will have an exceptional value for all producers of the excitation systems. Originality/value – The originality of the paper represents the development of the new robust sliding mode PSS and qualitative assessment of the developed stabilizer with two competitive stabilizers, i.e. the conventional linear- and advanced direct adaptive-PSS.